Clearing and settlement of derivatives - Loader, David
This book makes the reader aware of the background to the derivatives markets, how they have developed and their importance today. Clearing and Settlement of Derivatives addresses how and why derivative products are used and how the industry is structured, looking at both the exchange and over-the-counter markets. The role of the various parties is explained and the interaction between securities, commodities and derivatives explored. The key regulation that affects the use of derivatives by banks, corporate companies, institutional investors and private clients is covered and by way of example, the book reviews the various Directives affecting investment funds use of derivatives, capital adequacy requirements on banks and guidelines for private client use. The regulations looked at will be international, making this book suitable for most UK, European, and North American markets. * Informs and educates the reader about derivative products and everything that happens when trades take place without using confusing technical detail and unexplained jargon * Explains the background to derivatives and the market infrastructures and regulation in a clear and easy to read way * Deals with the extensive procedures and processes involved in lively, easy to follow "road maps."